Safflower as an alternate crop to chickpea under rainfed black soils of Prakasam district of Andhra Pradesh: SAFFLOWER AS AN ALTERNATE CROP TO CHICKPEA UNDER BLACK SOILS OF ANDHRA PRADESH - SAHAJA DEVA; G M V PRASADA RAO; CH VARAPRASADA RAO (Journal of Oilseeds Research, 2019)
Chickpea is a major rabi season crop in Prakasam district of Andhra Pradesh but suffers from moisture stress if there is less (<350 mm) rainfall during crop growth. Safflower (Carthamus tinctorius L.), commonly known as kardi is one ofthe important rabi oilseed crops ofthe country and is expected to withstand moisture stress better with a requirement of around 250 mm rainfall. Earlier study had indicated that safflower could be an alternative crop to chickpea in Prakasam district. Under the present investigation, on-farm-trials were conducted with farmers to compare the performance of safflower improved varieties against the chickpea local variety. Two year study has indicated that safflower could be an alternate crop to chickpea in the rainfed black soils of Prakasam district. Therefore, safflower can play an important role in crop diversification in low rainfall areas and in areas like Prakasam district where rabi crops suffer from terminal moisture stress.